2018
DOI: 10.3389/fcvm.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Mechanisms of Exercise-Induced Cardiac Remodeling

Abstract: Exercise has a myriad of physiological benefits that derive in part from its ability to improve cardiometabolic health. The periodic metabolic stress imposed by regular exercise appears fundamental in driving cardiovascular tissue adaptation. However, different types, intensities, or durations of exercise elicit different levels of metabolic stress and may promote distinct types of tissue remodeling. In this review, we discuss how exercise affects cardiac structure and function and how exercise-induced changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 272 publications
(264 reference statements)
2
58
0
2
Order By: Relevance
“…The presence of LDH within mitochondria could be particularly important to the heart, which has high energetic requirements that further increase with exercise. The rationale for examining mLDH is strengthened by the fact that circulating lactate concentration correlates positively with myocardial lactate uptake and oxidation [3,18,19] and can contribute remarkably to cardiac ATP production in mammals [2]. Importantly, any NADH generated within mitochondria during the LDH reaction would be directly available to the respiratory chain, bypassing the need to transport reducing equivalents across the inner mitochondrial membrane via the malate-aspartate shuttle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of LDH within mitochondria could be particularly important to the heart, which has high energetic requirements that further increase with exercise. The rationale for examining mLDH is strengthened by the fact that circulating lactate concentration correlates positively with myocardial lactate uptake and oxidation [3,18,19] and can contribute remarkably to cardiac ATP production in mammals [2]. Importantly, any NADH generated within mitochondria during the LDH reaction would be directly available to the respiratory chain, bypassing the need to transport reducing equivalents across the inner mitochondrial membrane via the malate-aspartate shuttle.…”
Section: Discussionmentioning
confidence: 99%
“…Results of our exercise capacity tests indicated that lactate abundance negatively correlated with running distance only in untrained mice, which suggests potential adaptations to circulating lactate. Because the heart strongly adapts to exercise [2], is a net lactate consumer [2], and is a primary contributor to exercise capacity [20], we tested whether exercise influences lactate-supported respiration in isolated heart mitochondria. In both cardiac and skeletal muscle mitochondria, lactate failed to support significant amounts of respiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous epidemiological studies have convincingly demonstrated the beneficial effect of physical exercise on CVD outcomes, and thus, it has been considered as a valuable therapeutic approach for CVDs [56,[66][67][68][69]. The favorable effect of regular exercise on CVDs progress is primarily attributed on the exercise-mediated enhancement of the antioxidant capacity and reduction of oxidative stress levels that subsequently results in redox balance preservation and cellular homeostasis [63,64].…”
Section: Exercise Cardiovascular Disease and Oxidative Stressmentioning
confidence: 99%
“…In a study of myocardial gene expression profile in rats, it was shown that during exercise-induced physiological myocardial hypertrophy, the glucose signal of cardiomyocytes was significantly different, while there was no significant change in pathological hypertrophy ( Kong et al., 2005 ). A large number of studies have proved that the metabolic coordination is an essential condition for myocardial adaptive growth ( Turpeinen et al., 1996 ; Peterzan et al., 2017 ; Fulghum and Hill, 2018 ; Gibb and Hill, 2018 ; Heallen et al., 2020 ), but it is not clear whether the regulation of myocardial energy metabolism can reverse myocardial remodeling and improve myocardial function. Therefore, the study of energy metabolism in exercise-induced physiological cardiac hypertrophy is beneficial to the exploration of exercise-induced cardiac adaptation and might be a unique research perspective for interventions in heart failure and other cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%